2001
DOI: 10.3354/meps220219
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preferences and performance of a marine isopod on seaweed hosts: cost of habitat specialization

Abstract: The evolutionary hypotheses on plant-herbivore interaction assume that plant secondary compounds, such as the phlorotannins of brown algae, function as feeding deterrents for herbivores. We studied the effect of seaweed quality on the feeding preferences and performance of the isopod Idotea baltica. We offered I. baltica 6 species of algae, abundant in the Fucus vesiculosus belts where this mesograzer lives, in simultaneous preference tests. The tests were conducted both with natural algae and with artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 49 publications
1
77
0
2
Order By: Relevance
“…From this, we could expect that these species search for specific food items such as microbial colonization of the food. However, Jormalainen et al (2001) suggested that in I. balthica, habitat structure, in terms of predation avoidance, and the spatiotemporal stability of the habitat are more important factors selecting for feeding preferences than the quality of the food.…”
Section: Fig 4 Dietary Contributions (%) Of the Four Potential Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…From this, we could expect that these species search for specific food items such as microbial colonization of the food. However, Jormalainen et al (2001) suggested that in I. balthica, habitat structure, in terms of predation avoidance, and the spatiotemporal stability of the habitat are more important factors selecting for feeding preferences than the quality of the food.…”
Section: Fig 4 Dietary Contributions (%) Of the Four Potential Foodmentioning
confidence: 99%
“…Hence, the coexistence of these species in the same biotope raised the question about trophic diversity in this particular environment. To our knowledge, no data are available about the feeding ecology of I. hectica and C. prismatica, while I. balthica food includes both vegetable (plant and algae) and animal materials (Naylor 1955;Nicotri 1980;Jormalainen et al 2001). Laboratory observations suggested that I. balthica actively consume living and decaying P. oceanica material (Lorenti and Fresi 1983b).…”
Section: Introductionmentioning
confidence: 99%
“…After the juvenile stage its diet consists mainly of Fucus vesiculosus (Salemaa 1987, Schaffelke et al 1995, Jormalainen et al 2001a) and, to a lesser extent, of filamentous epiphytic algae. The presence of I. baltica in F. vesiculosus habitats is highly variable over the course of the year.…”
Section: Study Organisms Fucus Vesiculosus L (Phaeophyceaementioning
confidence: 99%
“…Large and efficient herbivore species such as sea urchins, periwinkles or limpets are lacking and the low diverse communities are often dominated by resource generalists such as gammarid amphipods and idoteids (Salemaa 1979;Jormalainen et al 2001;Orav-Kotta and Kotta 2003). The native Gammarus salinus Spooner and the invasive Gammarus tigrinus Sexton are the prevailing gammarid amphipods in the coastal range of the northern Baltic Sea (Hällfors et al 1981;Herkül and Kotta 2007).…”
Section: Introductionmentioning
confidence: 99%